Cost effectiveness and cost-utility analysis of a group-based diet intervention for treating major depression – the HELFIMED trial. (2nd October 2020) - Segal, Leonie; Twizeyemariya, Asterie; Zarnowiecki, Dorota; Niyonsenga, Theo; Bogomolova, Svetlana; Wilson, Amy; O'Dea, Kerin; Parletta, Natalie
ABSTRACT: Background/objectives: Major depression has a negative impact on quality of life, increasing the risk of premature death. It imposes social and economic costs on individuals, families and society. Mental illness is now the leading cause globally of disability/lost quality life and premature mortality. Finding cost-effective treatments for depression is a public health priority. We report an economic evaluation of a dietary intervention for treating major depression. Methods: This economic evaluation drew on the HELFIMED RCT, a 3-month group-based Mediterranean-style diet (MedDiet) intervention (including cooking workshops), against a social group-program for people with major depression. We conducted (i) a cost-utility analysis, utility scores measured at baseline, 3-months and 6-months using the AQoL8D, modelled to 2 years (base case); (ii) a cost-effectiveness analysis, differential cost/case of depression resolved (to normal/mild) measured by the DASS. Differential program costs were calculated from resources use costed in AUD2017. QALYs were discounted at 3.5%pa. Results: Best estimate differential cost/QALY gain per person, MedDiet relative to social group was AUD2775. Probabilistic sensitivity analysis, varying costs, utility gain, model period found 95% likelihood cost/QALY less than AUD20, 000. Estimated cost per additional case of depression resolved, MedDiet group relative to social group was AUD2, 225. Conclusions: A MedDiet group-program for treating major depression was highly cost-effective relative to a social group-program, measured in terms of cost/QALY gain and cost per case of major depression resolved. Supporting access by persons with major depression to group-based dietary programs should be a policy priority. A change to funding will be needed to realise the potential benefits.